Pathophysiology, diagnosis and management of peripartum cardiomyopathy: a position statement from the Heart Failure Association of the European Society of Cardiology Study Group on peripartum cardiomyopathy - Bauersachs, Johann; König, Tobias; Meer, Peter; Petrie, Mark C.; Hilfiker‐Kleiner, Denise; Mbakwem, Amam; Hamdan, Righab; Jackson, Alice M.; Forsyth, Paul; Boer, Rudolf A.; Mueller, Christian; Lyon, Alexander R.; et al. (European journal of heart failure, 2019)
Peripartum cardiomyopathy (PPCM) is a potentially life‐threatening condition typically presenting as heart failure with reduced ejection fraction (HFrEF) in the last month of pregnancy or in the months following delivery in women without another known cause of heart failure. This updated position statement summarizes the knowledge about pathophysiological mechanisms, risk factors, clinical presentation, diagnosis and management of PPCM. As shortness of breath, fatigue and leg oedema are common in the peripartum period, a high index of suspicion is required to not miss the diagnosis. Measurement of natriuretic peptides, electrocardiography and echocardiography are recommended to promptly diagnose or exclude heart failure/PPCM. Important differential diagnoses include pulmonary embolism, myocardial infarction, hypertensive heart disease during pregnancy, and pre‐existing heart disease. A genetic contribution is present in up to 20% of PPCM, in particular titin truncating variant. PPCM is associated with high morbidity and mortality, but also with a high probability of partial and often full recovery. Use of guideline‐directed pharmacological therapy for HFrEF is recommended in all patients respecting contraindications during pregnancy/lactation. The oxidative stress‐mediated cleavage of the hormone prolactin into a cardiotoxic fragment has been identified as a driver of PPCM pathophysiology. Pharmacological blockade of prolactin release using bromocriptine as a disease‐specific therapy in addition to standard therapy for heart failure treatment has shown promising results in two clinical trials. Thresholds for devices (implantable cardioverter‐defibrillators, cardiac resynchronization therapy and implanted long‐term ventricular assist devices) are higher in PPCM than in other conditions because of the high rate of recovery. The important role of education and counselling around contraception and future pregnancies is emphasised.